Early medieval ‘places and spaces’: breaking down boundaries in British archaeology - Hamerow, H (Archaeopress Publishing, 2018)
British medieval archaeology is becoming increasingly integrated as new methodologies, research programmes and data sets encourage researchers to cross the boundaries between the study of settlements, burials, and landscapes. This paper reviews, through a series of case studies, new approaches to 'social landscapes' and in particular assembly sites, including fairs, legal assemblies, cemeteries and places of execution. These studies illustrate how a greater willingness to 'trespass' into other disciplines such as place‐name studies and legal history is yielding new insights into the archaeological record. The paper concludes that it is becoming increasingly difficult to separate the study of early medieval burial, settlement and landscape into distinct sub‐disciplines, especially for the period between c 600‐1000, a time when conceptions of 'community' were rapidly changing.